2017
DOI: 10.1007/s10029-017-1644-5
|View full text |Cite
|
Sign up to set email alerts
|

Single center experience with the modified retromuscular Sugarbaker technique for parastomal hernia repair

Abstract: The outcomes of the retromuscular Sugarbaker technique for the management of parastomal hernias have been disappointing at our institution, with a concerning rate of serious mesh-related complications. This operation, as originally described, needs further study before widespread adoption with a particular focus on the technique of mesh placement, the most appropriate mesh selection, and the long-term rate of mesh erosion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 21 publications
1
32
0
1
Order By: Relevance
“…However, this technique also has three shortcomings: (a) potential mesh‐related complications and erosion of the bowel, 5 (b) lack of data concerning long‐term outcomes, 4 and (c) technical difficulty. With regard to difficulty, Pauli parastomal hernia repair should not be performed by someone unfamiliar with TAR and Sugarbaker repair techniques 4 …”
Section: Discussionmentioning
confidence: 99%
“…However, this technique also has three shortcomings: (a) potential mesh‐related complications and erosion of the bowel, 5 (b) lack of data concerning long‐term outcomes, 4 and (c) technical difficulty. With regard to difficulty, Pauli parastomal hernia repair should not be performed by someone unfamiliar with TAR and Sugarbaker repair techniques 4 …”
Section: Discussionmentioning
confidence: 99%
“…Population-based studies on incidence and prevalence of PSH are rare, and studies on rate of PSH repair are even rarer (4,5). However, there is an abundance of studies describing outcome of elective PSH repair, though these are often from a single center, describing a specific method of repair often with specific prosthetic material (6)(7)(8). Recurrence rates after PSH surgery in modern studies range from 3% to 22% (7)(8)(9)(10).…”
Section: Original Research Articlementioning
confidence: 99%
“…However, there is an abundance of studies describing outcome of elective PSH repair, though these are often from a single center, describing a specific method of repair often with specific prosthetic material (6)(7)(8). Recurrence rates after PSH surgery in modern studies range from 3% to 22% (7)(8)(9)(10). Furthermore, there are few studies on emergency PSH repair, and these have shown high complication rates, including a 13.2% reoperation rate and 6.3% mortality rate, both at 1 month (4)(5)(6).…”
Section: Original Research Articlementioning
confidence: 99%
“…Extraperitoneal mesh placement by laparoscopy can improve the surgical results and achieve a better clinical outcome while reducing the overall cost of treatment. The totally endoscopic sublay (TES) technique has been previously described ( 11 ) and extraperitoneal/sublay parastomal hernia repair has been explored in open, laparoscopic, endoscopic, and robotic surgeries ( 12 17 ). Here we present a case of a 74-year-old patient with parastomal hernia and a history of open radical resection treated with a totally extraperitoneal (TEP) endoscopic approach, with a good clinical outcome.…”
Section: Introductionmentioning
confidence: 99%